ChemInform Abstract: Visible‐Light‐Responsive β‐Rhombohedral Boron Photocatalysts. Issue 38 (30th August 2013) - Liu, Gang; Yin, Li‐Chang; Niu, Ping; Jiao, Wei; Cheng, Hui‐Ming
Abstract Commercially available β‐rhombohedral boron crystals (sub‐micrometer‐ and micrometer‐sized) with and without an amorphous oxide layer on their surface are photocatalytically active under visible light irradiation as evidenced by their ability to generate OH radicals in terephthalic acid suspensions.